Pengembangan Google Sites Terintegrasi Zep Quiz Untuk Meningkatkan Understanding Ability Siswa Kelas VII SMP Pada Materi Aljabar - anthony hiu; Muchtadi muchtadi (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2026)
Abstract: Low algebraic understanding among Grade VII students remains a persistent challenge in Indonesian secondary mathematics education. This study developed Google Sites integrated with Zep Quiz to enhance students' understanding ability in algebra. Using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), the study involved six expert validators and 30 Grade VII students at SMP Negeri 2 Pontianak. Instrument content validity was confirmed via Aiken's V (0.82–0.93) and empirical validity (r = 0.86–0.98; α = 0.945). Expert validation yielded an overall validity score of 89.99% (highly valid: media 85.66%, content 94.33%). Practitioner ratings reached 94.67% (highly practical: students 89.33%, teacher 100%). Effectiveness was assessed via Wilcoxon Signed Rank Test (z = −4.782; p < 0.001). Mean scores rose from 25.33 (pretest) to 79.07 (posttest), producing an overall N-Gain of 0.72 (high category). Indicator-level analysis showed N-Gain values ranging from 0.55 (applying concepts algorithmically) to 0.84 (solving contextual problems). These findings suggest that integrating Google Sites with gamified formative assessment via Zep Quiz substantially improves algebraic understanding ability in early secondary school students. Keywords: ADDIE model, algebra, gamification, Google Sites, understanding ability, Zep Quiz